TINGKAT KEPUASAN KONSUMEN TERHADAP OLAHAN HASI PERIKANAN FESTIVAL BAZAR FAKULTAS PERTANIAN UNIVERSITAS PGRI BANYUWANGI - Arfiati, Arfiati Ulfa Utami; Chastelyna, Agnes Juniarti; Setyawan, Bagus (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2023)
The purpose of this study was to determine the level of consumer satisfaction with processed fishery products at the bazaar festival at the Faculty of Agriculture, University of PGRI Banyuwangi. This study uses a quantitative model with a survey method. The research respondents totaled 100 consumers consisting of students lecturers and staff of the University of PGRI Banyuwangi. The results showed that the percentage of consumer satisfaction with product quality was 70%, the consumer satisfaction level with customer service quality was 65%, and the consumer satisfaction level with product price was 65% and could be categorized as satisfied.